Políticas del Control de Efectivo en la Lubricadora y Lavadora “SAN JUAN - Vaca Vera, Grey Celena (2018)
Currently, most companies perform procedures or functions of irregular shape, affecting in such way the growth and success of it; that is why it is It is fundamental to establish adequate control policies and to ensure regularly that these processes are being executed in a timely manner, since the application of these regulates the acts of administration, management and conditions that must be met. The purpose of this case study is to identify the existence and application of of control policies for cash management in the "SAN JUAN" Lubricator and Washer, since effective management control helps achieve financial goals established, guarantees the reliability and accuracy of the financial information; taking in account that cash within a company is the most liquid current assets that It allows to cover obligations and make immediate payments. It should be noted that every company regardless of the economic activity that carries out requires efficient control procedures that contribute to the prevention of errors and allow to protect and safeguard the income obtained by marketing, production or service that it provides, for this reason, it is important to establish clear guidelines and precise in order to define the transparency of the procedures in the personnel of the area administrative - accounting